Gender differences in temporal relationships between gambling urge and cognitions in treatment-seeking adults. (April 2018) - Dunsmuir, Phoebe; Smith, David; Fairweather-Schmidt, A.Kate; Riley, Ben; Battersby, Malcolm
Abstract: Many gambling-specific CBT programs seek to target either gambling-related urge or cognitions or both. However, little is known of the influence of one symptom type on another across time and whether these differ for men and women help-seeking problem gamblers. The aim of this study was threefold: to determine presence of measurement invariance for urge and cognition measures over time; to investigate the effect of baseline urge on end-of-treatment gambling-related cognitions – and the reciprocal relationship; and, identify whether these pathways differ across gender. Self-reported gambling urge (GUS), and gambling-related cognitions (GRCS) data from treatment-seeking problem gamblers prior to and post treatment (N = 223; 62% men) were analyzed with cross-lagged panel models, moderated by gender. Conceptualization of urge and cognitions were found to be temporally stable. There was no significant association between baseline GUS scores and post-treatment GRCS scores, nor the reverse relationship. Putatively, this infers that coexisting urge and gambling-related cognition components of problem gambling operate independently over time. Analyses revealed gambling urge had a significantly stronger tracking correlation across time for men than women when adjusting for cognition paths. This investigation provides early evidence for tailoring CBT in response to sub-population gambling-related characteristics, demonstrated across men and women. Highlights: Urge and cognitive components are key constructs involved in problem gambling behavior. A cross-lagged panel design showed no significant association between baseline urge and end-of-treatment cognitions. Analogous analyses found no significant association between baseline cognitions and end-of-treatment urge. Results infer coexisting urge and gambling-related cognition components of problem gambling operate independently over time. A signficantly stronger relationship between urge at baseline and at end-of-treatment was identified for maless.